The use of heparin-containing lubricant in clinical practice - T.B. Romanova; M.H. Rabadanova; E.G. Rybakova; Z.U. Teviyeva; M.S. Gorshkova (РМЖ "Клиническая офтальмология")
T.B. Romanova1, M.G. Rabadanova1,2, E.G. Rybakova1, Z.U. Teviyeva1, M.S. Gorshkova2 1 Pirogov Russian National Research Medical University, Moscow 2 Municipal Clinical Hospital № 15 named after O. M. Filatov, Moscow This publication is a continuation of the article published in Clinical Ophthalmology № 3—2017. In this paper, we provide more detailed information on the symptoms and signs, that occur in the patients of the study group, and give some clinical cases. It bears reminding, that 30 people (60 eyes) were examined. All patients were examined and observed according to a single program, which included: collection of complaints and anamnesis, refractometry and visometry, tonometry, biomicroscopy, staining of the anterior segment of the eye with fluorescein and lissamine green, determination of invasive tear film break-up time and Schirmer test, filling in the McMonnis questionnaire about the dry eye symptoms. All patients used the heparin-containing lubricant PARIN-POS («URSAFARM Artzneimittel GmbH, Germany), which is a sterile eye ointment, 1 gram of which contains 1300 IU of animal heparin. The following clinical cases of patients with DES are considered: 1. a student, an active user of electronic gadgets; 2. An accountant who spends a lot of time at the computer and has been wearing soft contact lenses for 17 years. 3. A patient suffering from pemphigus, with a purulent ulcer of the cornea OS and acute infiltrative keratitis OD. Key words: «dry eye» syndrome, tear film, artificial tears, fluorescein, lissamine green. For citation: Romanova T.B., Rabadanova M.G., Rybakova E.G. et al. The use of heparin-containing lubricant in clinical practice // RMJ “Clinical ophthalmology”. 2018;1:60–64.